PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM GERAKAN DESA IKUT SEJAHTERA (GADIS) DI KABUPATEN PESAWARAN - Kaligis, Dendy Romadhona; Syafri, Wirman; Achmad, Mansur (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2021)
This research departed from the problem of organizing the GaDIS program, the Pesawaran District Government formed the GaDIS Financial Aid Coordination Team as the organization implementing GaDIS assistance under "supervise" and the responsibility of the Pesawaran Regent. In carrying out its duties, the Coordination Team is assisted by a Team Secretariat consisting of elements from the relevant regional apparatus. With this assistance, it is hoped that BUMDes can be empowered and productive, which in the end will present or generate income for the village, and then of course that income will have a positive and significant effect on the independence and welfare of the village. The research method is basically a scientific way to obtain data with a specific purpose and use. The method chosen is closely related to the procedures, tools and research design used. The procedures and tools used in the research must match the research methods used. The implementation of the GaDIS Program which is held systematically, based on high-performing villages and prioritizes the type of business or potential based on village deliberations, indirectly gives a positive effect, namely stimulation to each other village that has not received the GaDIS Program to improve their performance and improve their government administration. as well as strengthening in many other lines of implementation, so that in the future it is hoped to be able to obtain the GaDIS Program for strengthening in other economic fields. This is of course in line with the definition and thought that public policy is a program projected from goals, values ​​and practices. A policy choice is made to lead to the use of public power to influence the lives of citizens. But on the other hand, the lack of institutional strengthening and the low capacity of human resources for BUMDes management, as well as the low accessibility and action, have also resulted in low improvements in business, income and community improvement. This is at least experienced by Caringin Village, Way Ratai District, which was found by researchers in the field.